Prolonged Survival Outcome in a Patient with Refractory Metastatic Colorectal Cancer Treated with Regorafenib Plus 5-Fluorouracil: A Case Report and Literature Review - Abdullah Esmail; Bayan Khasawneh; Ebtesam Al-Najjar; Raed Zaidan; Maen Abdelrahim (Reports)
Background: The use of regorafenib and 5-fluorouracil in the management of refractory metastatic colorectal cancer has gained increasing attention due to their demonstrated efficacy in extending the survival of patients with colorectal cancer. This study aims to discuss the effect of using regorafenib and 5-fluorouracil combination therapy in refractory metastatic colorectal cancer patients. Case Presentation: We present a case report of a 68-year-old female patient with KRAS G12D and PIK3CA mutations who was diagnosed with stage IV-C colon cancer. She was referred to hospice care and subsequently received therapeutic intervention with 56 cycles of regorafenib and 5-fluorouracil for 31 months while maintaining stable disease (SD). The patient exhibited good tolerance with minimal adverse effects, including Grade I-II Hand–Foot Syndrome. Conclusions: Our case showed the feasibility of using Regorafenib and 5-fluorouracil combination therapy in stage IV refractory metastatic colorectal cancer treatment, which resulted in an improvement in the overall survival after she was referred to Hospice care. Utilizing this case report may provide valuable input in managing refractory metastatic colorectal cancer, given the prolonged survival and the clinical meaningfulness of this regimen in our patient.